Mortality rates and survival analysis of a cohort of owned adult dogs and puppies in Hluvukani Bushbuckridge South Africa - Knobel, Darryn Leslie (University of Pretoria, 2016)
Dissertation (MSc)--University of Pretoria, 2015.